Measuring Employment: Experimental Evidence from Urban Ghana. (12th June 2020) - Heath, Rachel; Mansuri, Ghazala; Rijkers, Bob; Seitz, William; Sharma, Dhiraj
Abstract: Using a randomized survey experiment in urban Ghana, this paper demonstrates that the length of the reference period and the interview modality (in-person or over the phone) affect how people respond in labor surveys, with impacts varying markedly by job type. Survey participants report significantly more self-employment spells when the reference period is shorter than the traditional one week, with the impacts concentrated among those in home-based and mobile self-employment. In contrast, the reference period has no impact on the incidence of wage-employment. The wage-employed do report working fewer days and hours when confronted with a shorter reference period. Finally, interviews conducted on the phone yield lower estimates of employment, hours worked, and days worked among the self-employed who are working from home or a mobile location as compared to in-person interviews.